Un año a destiempo. Anécdota e historia literaria - Carlos Walker (Cuadernos LIRICO)
This paper develops theoretical-critical foundations for a study of 1969 Argentine literature. To this end, we examine some approaches to the representation of time proper to literary history and certain results obtained by other historical studies focused on specific years.Based on the characteristics of 1969 in Argentine, we present two complementary ways to show how this literary history research is organized. First, Dolf Oehler's study, Juin 1848, le spleen contre l'oubli, is analyzed as a cross between the history of ideas and literary history. Secondly, we turn to the essay by Pablo Oyarzún, El dedo de Diógenes. La anécdota en filosofía, which reflects on the different modalities of the history of philosophy. All this allows us to show the leading role played by the anecdote in this research.